Development of Computer Multimedia to Enhance English for Communication of Grade 6 Students - Utsakarn, Kanatip; Chorum, Wanvisa (Ratchaphruek Journal, 2023)
This quasi-experimental research had objectives for: 1) To develop the computer multimedia to enhance English for communication of grade 6 students with the efficiency at 75/75; 2) To compare achievement of speaking and listening skills in English of students learning by using multimedia lessons and traditional method; and 3 To study the student’s satisfaction that learning by using multimedia lessons. The seventy samples were used in this research by cluster random sampling from 206 students of Wangrongnoi school, Sub-tai school, Wangrongyaisamukkee and Nongkratoom school Nakhon Ratchasima Province. The sample divided to group; one for efficiency testing (30 cases of Barnsub-tai and Wangrongyaisamukkee school) and the other two groups; experimental group (20 cases of Wangrongnoi school) and control group (20 cases of Nongkratoom school). The treatment was computer multimedia, two lesson plans, the English test, and the learning satisfaction test. Data were analyzed by mean, standard deviations, and t-test for independent. The findings were: 1) The efficiency of the computer multimedia was 76.32/ 75.43, 2) The student’s speaking and listening skills in English using by the computer multimedia lessons to improve English skills for communication were significantly higher than those students who learned by traditional method at the .05 level, and 3) The students’ satisfaction towards learning by using the computer multimedia lessons to improve English skills for communication was rated at high level.